Enhanced Cycling Performance for Lithium–Sulfur Batteries by a Laminated 2D g‐C3N4/Graphene Cathode Interlayer. Issue 1 (28th November 2018) - Qu, Long; Liu, Pei; Yi, Yikun; Wang, Tao; Yang, Pu; Tian, Xiaolu; Li, Mingtao; Yang, Bolun; Dai, Sheng
Abstract: Decay in electrochemical performance resulting from the "shuttle effect" of dissolved lithium polysulfides is one of the biggest obstacles for the realization of practical applications of lithium–sulfur (Li–S) batteries. To meet this challenge, a 2D g‐C3 N4 /graphene sheet composite (g‐C3 N4 /GS) was fabricated as an interlayer for a sulfur/carbon (S/KB) cathode. It forms a laminated structure of channels to trap polysulfides by physical and chemical interactions. The thin g‐C3 N4 /GS interlayer significantly suppresses diffusion of the dissolved polysulfide species (Li2 S x ; 2< x ≤8) from the cathode to the anode, as proven by using an H‐type glass cell divided by a g‐C3 N4 /GS‐coated separator. The S/KB cathode with the g‐C3 N4 /GS interlayer (S/KB@C3 N4 /GS) delivers a discharge capacity of 1191.7 mAh g −1 at 0.1 C after 100 cycles, an increase of more than 90 % compared with an S/KB cathode alone (625.8 mAh g −1 ). The S/KB@C3 N4 /GS cathode shows good cycling life, delivering a discharge capacity as high as 612.4 mAh g −1 for 1 C after 1000 cycles. According to XPS results, the anchoring of the g‐C3 N4 /GS interlayer to Li2 S x can be attributed to a coefficient chemical binding effect of g‐C3 N4 and graphene on long‐chain polysulfides. Generally, the improvement in electrochemical performance originates from a coefficient of the enhanced Li + diffusion coefficient, increased charge transfer, and the weakening of the shuttle effect of the dissolved Li2 S x as a result of the g‐C3 N4 /GS interlayer. Abstract : The "shuttle effect" of dissolved lithium polysulfides is one of the biggest obstacles for the realization of practical applications of Li–S batteries. A laminated g‐C3 N4 /GS interlayer firmly anchors polysulfide by physical and chemical interactions, constructing a 3D network of charge transfer, which results in an ultralong cycling life of the S/KB@C3 N4 /GS cathode, enhancing electrochemical performance.